HUBUNGAN KUALITAS PELAYANAN GAWAT DARURAT DENGAN TINGKAT KEPUASAN PASIEN PENGGUNA BPJS KESEHATAN DI IGD RSI UNISMA MALANG - Ikhda Ulya; Melli Anggraeni; Dewi Kartikawati Ningsih (Universitas Harapan Bangsa Purwokerto, 2017)
Background : BPJS Health as a legal body health insurance providers continue to develop themselves to serve the basic needs of public health. But in its development there are still some obstacles that can affect user satisfaction, especially in the field of emergency services. Objective: To analyze the relationship quality of emergency services with the level of satisfaction patient BPJS Health at RS Unisma Malang. Method : This research design using cross sectional approach. Determination of sample by using purposive sampling technique with number of 144 respondents. Results : Spearman's Rho did got p-value 0.000 (<0,05) it’s mean that there are relation between quality of emergency service with patient satisfaction level of BPJS. Correlation coefficient value of 0.810, the meaning of the relationship of emergency service quality with patient satisfaction level BPJS included in the category very strong with the direction of a positive relationship. The better quality of emergency services will increase patient satisfaction. Conclusion: There is a relationship between the quality of emergency services to the level of patient satisfaction BPJS Health at RS Unisma Malang. so, the hospital is expected to maintain and improve the quality of emergency services provided, so that the level of patient satisfaction BPJS Health well maintained. Keywords: Emergency Service Quality, Patient Satisfaction Level, BPJS Health.